2022
DOI: 10.1186/s13034-022-00453-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effects of exercise on depression in adolescents

Abstract: Background Depression is widespread among adolescents and seriously endangers their quality of life and academic performance. Developing strategies for adolescent depression has important public health implications. No systematic review on the effectiveness of physical exercise for adolescents aged 12–18 years with depression or depressive symptoms has previously been conducted. This study aims to systematically evaluate the effect of physical exercise on adolescent depression in the hope of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 98 publications
(94 reference statements)
1
35
0
Order By: Relevance
“…Electroconvulsive shock therapy, exercise or endurance and muscle-strengthening training are also considered treatments for depression in adults, and these treatments are also applicable in the treatment of depression in adolescents ( Strohle, 2009 ; Wachtel et al, 2011 ; Hughes et al, 2013 ; Gokce et al, 2019 ; Wang et al, 2022 ). These treatments have shown positive effects on adolescent depression, and BDNF has been considered to play a role in their antidepressant actions ( Tsai et al, 2010 ; Murawska-Ciałowicz et al, 2021 ).…”
Section: Brain-derived Neurotrophic Factor In the Treatment Of Adoles...mentioning
confidence: 99%
“…Electroconvulsive shock therapy, exercise or endurance and muscle-strengthening training are also considered treatments for depression in adults, and these treatments are also applicable in the treatment of depression in adolescents ( Strohle, 2009 ; Wachtel et al, 2011 ; Hughes et al, 2013 ; Gokce et al, 2019 ; Wang et al, 2022 ). These treatments have shown positive effects on adolescent depression, and BDNF has been considered to play a role in their antidepressant actions ( Tsai et al, 2010 ; Murawska-Ciałowicz et al, 2021 ).…”
Section: Brain-derived Neurotrophic Factor In the Treatment Of Adoles...mentioning
confidence: 99%
“…Exercise interventions are among the most studied adjunctive therapies and have proven very effective in reducing symptoms of anxiety and depression in pediatric populations. Furthermore, studies have shown a significantly higher adherence to exercise treatment interventions in adolescents as compared to psychological and drug therapies [39]. Yoga is particularly effective in the reduction of symptoms of anxiety [39,40].…”
Section: Exercise Interventionsmentioning
confidence: 99%
“…Furthermore, studies have shown a significantly higher adherence to exercise treatment interventions in adolescents as compared to psychological and drug therapies [39]. Yoga is particularly effective in the reduction of symptoms of anxiety [39,40]. For the most significant improvement, one study recommended participating in yoga sessions at least four times a week for at least six weeks [40].…”
Section: Exercise Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering together that mBDNF is a well-recognized myokine whose expression is increased after exercise, muscle-derived mBDNF is secreted into the circulation [ 68 ]. Although Pardridge et al demonstrated that BDNF in blood was rapidly degraded and no mBDNF transcytosis through the blood–brain barrier (BBB) in rat was observed [ 139 ], later studies showed that blood-borne mBDNF can enter the CNS by a rapid, saturable transport system of the BBB [ 140 , 141 ], mBDNF concentration in blood is reduced in psychiatric and neurological disorders [ 142 ], and physical exercise is an effective means to alleviate the mental dysfunction in a lot of psychiatric diseases [ 143 ]. Thus, it is tempting to hypothesize that peripheral mBDNF is a beneficial “exerkine” to improve the mental health.…”
Section: Unresolved Questionsmentioning
confidence: 99%